Sustained-Release Microspheres of Rivoceranib for the Treatment of Subfoveal Choroidal Neovascularization - E Seul Kim; Min Sang Lee; Hayoung Jeong; Su Yeon Lim; Doha Kim; Dahwun Kim; Jaeback Jung; Siyan Lyu; Hee Joo Cho; Dong Min Kim; Wonhee Suh; Ji Hoon Jeong (Pharmaceutics, 2021)
The wet type of age-related macular degeneration (AMD) accompanies the subfoveal choroidal neovascularization (CNV) caused by the abnormal extension or remodeling of blood vessels to the macula and retinal pigment epithelium (RPE). Vascular endothelial growth factor (VEGF) is known to play a crucial role in the pathogenesis of the disease. In this study, we tried to repurpose an investigational anticancer drug, rivoceranib, which is a selective inhibitor of VEGF receptor-2 (VEGFR2), and evaluate the therapeutic potential of the drug for the treatment of wet-type AMD in a laser-induced CNV mouse model using microsphere-based sustained drug release formulations. The PLGA-based rivoceranib microsphere can carry out a sustained delivery of rivoceranib for 50 days. When administered intravitreally, the sustained microsphere formulation of rivoceranib effectively inhibited the formation of subfoveal neovascular lesions in mice.